Design composite oxide supported Pt catalyst for catalytic wet air oxidation of ammonia with a high concentration in chloride system. Issue 20 (15th October 2022) - Feng, Bingxiao; Hao, Lining; Wang, Jiaqiang; Gai, Chaojie; Gai, Hengjun; Xiao, Meng; Huang, Tingting; Zhu, Quanhong; Song, Hongbing
Abstract: Massive discharge of ammonia nitrogen wastewater not only causes eutrophication of the water body but also has a toxic effect on humans and living things. How to deal with ammonia nitrogen wastewater is a crucial topic for researchers. Here, a novel catalyst of Pt@Ti–Si where platinum was supported on a composite oxide of titanium oxide (TiO2 ) and silicon oxide (SiO2 ) via a one-pot method was successfully synthesized for catalytic wet air oxidation (CWAO) of ammonia with a high concentration (more than 2000 ppm). Due to the improved specific surface area of SiO2 and the excellent acid-base resistance of TiO2, the prepared composite oxide-supported platinum catalyst has excellent catalytic performance and good stability for CWAO with a high concentration of ammonia. At 200 °C and the O2 pressure of 2 MPa for 2 h, the 1%Pt@Ti10–Si1 catalyst has a 96.32% conversion of 2470 ppm ammonia and 97.15% selectivity to N2 and has good catalytic performance even after five cycles. Under the same reaction conditions, when the chloride concentration in the system is 3000–10000 ppm, the CWAO reaction can be inhibited at an early stage and promote conversion and selectivity at a later stage. The results show that the catalyst has good tolerance to chloride ions, and the treated ammonia nitrogen wastewater can be used for subsequent biochemical processes. Therefore, the developed novel catalyst in this study is effective for the CWAO of highly concentrated ammonia and has potential industrial application value. Graphical abstract: Image 1